THE INFLUENCE OF POLITICAL CONNECTIONS, GENDER DIVERSITY, PROFITABILITY, AND LEVERAGE ON TAX AGGRESSIVENESS: (Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange 2019 – 2023) - Noviani, Ni Nyoman; Sujana, I Ketut (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Tax aggression refers to the deliberate reduction of tax liabilities through strategic tax planning, which can be carried out within the bounds of the law (tax avoidance) or through illegal means (tax evasion). This study is aimed at gathering empirical evidence on the impact of political affiliations, gender diversity, profitability, and leverage on tax aggression. This study used a total of 56 samples to examine all property and real estate businesses that were listed on the Indonesia Stock Exchange from 2019 to 2023. A probability sampling method known as purposive sampling was used to choose the samples. The data was analysed using SPSS software and multiple linear regression analysis. The findings indicated that political connections and gender diversity were associated with lower levels of tax aggression, while profitability and leverage were linked to higher levels of tax aggression. The theoretical significance of this study lies in its validation of the theory of planned behavior and agency theory in demonstrating the impact of political connections, gender diversity, profitability, and leverage on tax aggression.